THE IMPLEMENTATION OF THE DASA DHARMA VALUES IN SOCIAL STUDIES LEARNING TO DEVELOP STUDENTS’ SOCIAL AWARENESS - Naufal Fikri Mutamam; Lusty Firmantika (SOSIOEDUKASI, 2025)
This study aimed at describing the implementation of the Dasa Dharma values in social studies learning and analyzing those implementations in terms of students’ social awareness. The study employed a qualitative method, gathering data through observation, interviews, and documentation. After acquiring the data, the model from Miles, Huberman, and Saldana was administered for analysis. The findings show that the implementation of the Dasa Dharma values in social studies learning was reflected in each process, that is, planning, implementation, and evaluation. Students’ attitude and behavior, specifically their willingness to assist their peers during class, their sensitivity to the social circumstances around them, and their ability to work well in groups, reflect the form or outcome of this implementation. This form of implementation represents the Dasa Dharma values related to social awareness, that is, values 2, 4, and 5. This research is novel in that it focuses on the Dasa Dharma values integrated into social studies learning to foster social awareness. This research can be used as a reference to demonstrate that Crandall's theory of social awareness is relevant for application in social studies learning, collaborating with the Dasa Dharma values.